Pengaruh Kebijakan Dividen, Kepemilikan Manajerial, Kepemilikan Institusional terhadap Nilai Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Puput Kurniawati; Anggit Dyah Kusumastuti; Annisa Indah Mutiasari (Jurnal Syntax Admiration, 2024)
This study aims to determine the influence of dividend policies, managerial ownership, and institutional ownership, both partially and simultaneously, on the value of banking sector companies listed on the IDX for the period 2018-2022. Sampling in this study uses a purposive sampling technique. So that research data was obtained as many as 140 data samples. The type of research used is quantitative and analytical observational research design with a cross-sectional approach, which is a study with the aim of analyzing the dynamics of inter-effects and effects, by collecting time-lapse data at a certain time (point time approach). The analysis methods used are multiple linear regression analysis, F test, t test, and determination coefficient (R2). The results of the partial study show that dividend policy has a positive and significant effect on the value of companies in the banking sector in Indonesia, in 2018-2022. Meanwhile, management ownership and institutional ownership have no effect on the value of banking sector companies in Indonesia in 2018-2022. Simultaneously, dividend policies, institutional ownership, and management ownership have a significant effect on the value of companies in the banking sector in Indonesia in 2018-2022. The determination coefficient shows the magnitude of the variation in the dependent variable due to the variation of the independent variable of 11.3% The change in the variation in the company's value is due to the influence of dividend policy, institutional ownership, and management ownership. While the remaining 88.7% was influenced by other variables outside this study. Such as fiscal, monetary, or national political stability in its influence on the rise and fall of the company's value.